Internet of Things Based Intelligent monitoring and Controlling of Poultry System on using Artificial Intelligence - Barsagadea, Ajay G.; Rumaleb, Aniruddha S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The poultry business in contemporary India is one of the most important and rapidly expanding sectors of the country’s agricultural economy. Increases in chicken production can be attributed to better manufacturing methods and more efficient agricultural methods. The importance of automation in the current world cannot be overstated, and neither can the rapid development of the Internet of Things (IoT) idea with Artificial Intelligence (AI). Using a certain method, manual tasks may be made fully automatic. Poultry farms can benefit from IoT-based operations when remote monitoring and repair are required, transforming them from traditional to cutting-edge operations that make extensive use of automation. In order to maintain and enhance chicken health, it is necessary to constantly check for changes in a number of variables. In this study, we propose and construct a low-cost Internet of Things (IoT)-based system for monitoring environmental factors in a chicken farm in real time, including temperature, humidity, ammonia levels, and light intensity. Information gleaned via sensors and continuous monitoring. By putting the planned system into action, we were able to evaluate its viability. Temperature and humidity levels, as well as their management, are the most important climatic parameters for a poultry farm’s output. The purpose of this project is to automate the operation of a chicken farm by utilising Internet of Things (IoT) technologies. Chicken health is maintained by careful monitoring of environmental conditions like temperature, humidity, light, and ammonia gas, as well as through the supervision of routine tasks like feeding, watering, and cleaning.